(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
Drought observation and analysis have a significant impact on lives and properties. This research aims to identify the drought trend with its spatiotemporal distribution in seven climatic zones of Bangladesh. Mann-Kendall test and Standardized Precipitation Index (SPI) were used to identify the trend and spatiotemporal phenomenon visualized by Inverse Distance Weighting Interpolation. The findings demonstrate a substantial declining drought trend for short-term period to annual of SPI-3, SPI-6 and SPI-12 concerning the northern part of the northern zone, north-western, western, southwestern, and south-central zones whereas only increasing trend among these zones are found for SPI-3 of south-central zone. Furthermore, southeastern and north eastern zone are found for increasing trend of drought vulnerabilities for all the classes of SPI-3, SPI-6 and SPI-12. The northern part of the northern zone, north western and western are found for highest drought prone zones as it obtained SPI-12 of >-0.026, >-0.024 and >- 0.025 respectively. The study recommends that mechanisms and maintenance for water management be taken in order to integrate drought response strategies for droughtprone climatic zones. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 1-16